(3GdMce HGdYOd hGdEfUGa GdQGaY ddNdGa ajeG hbY Hjf HYV YdeGA SLdeGSI ef GdGNJdGas - (3YHO Gddg Hf eMeO Hf CHj HcQ GdYHjOj,J (B1090 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg QSGdI SejJgG GdMce HGdYOd hGdEfUGa hQJHJgG Ydi SGHbI hCQHYI eWGdH s
(3BNQgG (B:s
(3aHYVgG eYOf GdfHhg HYVgG eYOf GdhdGjI s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(39 (3c(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds